Longitudinal Strength Analysis of a Container Ship under Sagging and Hogging Conditions Using the Finite Element Method - Indah Melati Suci; Sukarno; Muhammad Zubair Muis Alie (International Journal of Marine Engineering Innovation and Research, 2025)
This study analyzes the longitudinal strength of a container ship under hogging and sagging conditions using the Nonlinear Finite Element Analysis (NLFEA) method. Numerical modeling was performed on a single frame spacing of the container ship to evaluate the stress and deformation distribution due to longitudinal bending loads. A three dimensional finite element model was developed using SHELL181 elements in ANSYS software, employing large displacement static analysis. The results show that under hogging conditions, the deck experiences a maximum tensile stress of 410.28 N/mm², while the bottom structure undergoes a compressive stress of -405.93 N/mm². Under sagging conditions, the deck experiences a compressive stress of 279.91 N/mm², and the bottom experiences a tensile stress of -387.80 N/mm². The ultimate bending moments were 1.42 × 10¹³ Nmm for hogging and -1.21 × 10¹³ Nmm for sagging, indicating that the ship is more susceptible to structural failure under sagging conditions. These findings highlight the importance of considering both loading conditions in the structural design of container ships to ensure safety and operational efficiency.